Building qualitative research construct by conceptualizing theory and model of the literature review / Mazlina Pati Khan and Irni Eliana Khairuddin - Pati Khan, Mazlina; Khairuddin, Irni Eliana (UiTM Press, 2020)
This paper concentrates on the process of construct development for the qualitative research design. The aim of this paper is to represent a process in the developing research construct which specifies into (7) steps; identifying issues, formation of problem statement, development of research objectives, research question, literature review, building toward the development of the construct, building the protocol for data collection techniques from the identified construct until formulated the pattern of finding. To formulate the statement of problem three (3) elements had been addressed; research gap, significant and context of the study. The consolidation of the research objective and research question must be aligned with the issues that had been examined on the statement of the problem. In addition literature review carried out toward understanding further upon issues been studied where it able to identify the construct that underpinning the theoretical research framework.